Communication fabric MVS-Express - Elizarov, G.S.; Gorbunov, V.S.; Levin, V.K.; Korneev, V.V.; Sokolov, A.A.; Andryushin, D.V.; Klimov, Yu.A.; Lacis, A.O. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2012)
An approach to the development of the MVS-Express communication fabric using the direct routing of PCI Express packets is considered. A number of programming tools based on the partitioned global address space for computer systems with the MVS-Express communication fabric are proposed. The efficiency of the proposed hardware-software decisions is estimated.